Peer tutoring in consumer computing : doctoral thesis - Klemo, Vladimir 1983 (V. Klemo ; Fakultet elektrotehnike i računarstva, 2013)
SHORT SUMMARY: The thesis presents a framework for automation of consumer’s application consumption knowledge based on monitoring the knowledge automation process and recommendation of tutors with the required expertise. The research on peer tutoring in consumer computing focuses on identifying consumers whose help can be recommended in the process of application consumption knowledge automation. The primary goal of the research is to test the hypothesis that it is possible to identify consumers possessing the required tacit knowledge based on a reduced number of parameters used to represent consumers’ procedural knowledge. The tutor recommendation algorithm is researched and developed based on structural analysis and authorship identification of consumers’ applications. The tutor recommendation system is implemented and integrated into the consumer programming tool Geppeto. In order to demonstrate efficiency of developed framework, consumer study is performed in an environment that provides objective evaluation of the peer-tutoring framework. -